An altered cytotoxic program of CD8+ T-cells in HIV-infected patients despite HAART- induced viral suppression (2019)
ABSTRACT: Despite the suppression of viral replication induced by the highly active anti-retroviral ther- apy (HAART), an increased immune activation and inflammatory state persists in HIV- infected patients, contributing to lower treatment response and immune reconstitution, and development of non-AIDS conditions. The chronic activation and inflammation affect the functionality and differentiation of CD8+ T-cells, particularly reducing their cytotoxic capacity, which is critical in the control of HIV replication. Although previous studies have shown that HAART induce a partial immune reconstitution, its effect on CD8+ T-cells cytotoxic function, as well as its relationship with the inflammatory state, is yet to be defined. Here, we charac- terized the functional profile of polyclonal and HIV-specific CD8+ T cells, based on the expression of cell activation and differentiation markers, in individuals chronically infected with HIV, under HAART. Compared with seronegative controls, CD8+ T-cells from patients on HAART exhibited a low degranulation capacity (surface expression of CD107a), with consequent low secreted levels and high intracellular expression of granzyme B and per- forin. This degranulation defect was particularly observed in those cells expressing the acti- vation marker HLA-DR, which were further characterized as effector memory cells with high expression of CD57. The expression of CD107a, but not of granzyme B and perforin, in CD8+ T-cells from HIV-infected patients on HAART reached levels similar to those in sero- negative controls when the treatment duration was higher than 25 months. In addition, the expression of CD107a was negatively correlated with the expression of exhaustion markers on CD8+ T-cells and the plasma inflammatory molecule sCD14. Thus, despite HAART- induced viral suppression, CD8+ T-cells from HIV-infected patients have an alteration in their cytotoxic program. This defect is associated with the cellular activation, differentiation and exhaustion state, as well as with the inflammation levels, and can be partially recovered with a long and continuous treatment.